Sosialisasi Pembuatan Sistem Notulen Rapat pada Badan Pusat Statistik (BPS) Kabupaten Ngawi - Saifulloh; Alim Citra Aria Bima; Moh Rizal Bagus Cahyono Putro; Bryan Abel Maulana (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Efficient and structured management of meeting minutes is an important requirement in supporting administrative governance in various government agencies, including the Central Statistics Agency (BPS). However, the manual recording and archiving process often faces obstacles such as document irregularity, risk of data loss, and lack of time efficiency. To resolve problems at the Ngawi Central Statistics Agency (BPS), based on the results of observations and discussions, the objective of the activity was to develop a digital-based meeting minutes application designed to simplify the process of recording, storing and distributing meeting results.The results of the activity show that implementing this application is able to increase time efficiency in managing minutes by up to 60%, as well as reducing the risk of data loss thanks to a digital-based storage system. With the success of this implementation, 95% of socialization participants understood the flow of system performance and the use of the system was very user friendly